Why India matters - Chadda, Maya , 1943- (Lynne Rienner, 2014)
Why is India's rise on the world stage so controversial? How can a state that is losing authority to its regions at the same time grow in international importance? Exploring an apparent paradox, Maya Chadda shows how culture, politics, wealth, and policy have combined to forge a distinctive Indian path to power, both nationally and in the international arena